2017
DOI: 10.1371/journal.pone.0168445
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Individual, Social and Work Characteristics to Employee Mental Health in a Coal Mining Industry Population

Abstract: BackgroundEvidence regarding the extent of mental health problems and the associated characteristics within an employee population is necessary to inform appropriate and tailored workplace mental health programs. Mental health within male dominated industries (such as mining) has received recent public attention, chiefly through observations regarding suicide in such populations in Australia and internationally. Currently there is limited empirical evidence regarding the mental health needs in the mining indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 50 publications
5
65
0
5
Order By: Relevance
“…These arrangements can increase relationship and family strains, 8 , 9 sleep disturbances, 5 , 10 and risky behaviour, such as excessive drinking 2 , 11 . Male predominance in the resource and mining workforce (88%) 12 and their low rates of help‐seeking have motivated research into the risks of mental ill health in the FIFO population 13 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These arrangements can increase relationship and family strains, 8 , 9 sleep disturbances, 5 , 10 and risky behaviour, such as excessive drinking 2 , 11 . Male predominance in the resource and mining workforce (88%) 12 and their low rates of help‐seeking have motivated research into the risks of mental ill health in the FIFO population 13 …”
mentioning
confidence: 99%
“…2,11 Male predominance in the resource and mining workforce (88%) 12 and their low rates of help-seeking have motivated research into the risks of mental ill health in the FIFO population. 13 Several studies have found elevated rates of mental health problems among FIFO workers. 4,5,14,15 High rates of psychological distress in FIFO workers have been reported, 4,5 particularly in those on high compression rosters (1e4 weeks on/1 week off), 4,16,17 who report dissatisfaction with shift lengths, challenges in maintaining conflictfree relationships because of prolonged periods away from home, and lower levels of workelife balance than any other Australian industry group.…”
mentioning
confidence: 99%
“…Similarly in Yu et al study done in Shanxi, China among 540 workers 52.46% of workers out of 305 workers included in their study, work for more than 8hrs per day which is very high compared to our study were as in Considine study 86.5% of workers out of 1457 workers do work for more than 8 hrs per day which is very high compared to our study. 7,8 The probable reason could be strict labor laws in India to work not more than 8hrs per day or 48 hrs per week.…”
Section: Discussionmentioning
confidence: 99%
“…According to work experience 51.07% (41.85% underground workers + 9.22% surface workers) workers are having experience of working for 20-30 yrs and 38.30% (30.50% underground workers + 7.80%) workers are having experience of working for more than 30 yrs which shows that these workers are more exposed to coal dust for a long period and are more prone for chronic diseases when compared to Rajashekar et al 9 A study was done in 493 mine workers where there are no workers who had work experience for more than 20yrs and there are only 4.40% of workers having work experience for 11-20 yrs who are very less compared to our study also in Considine et al study there are only 37.7% of workers having work experience for more than 10 yrs. 7 In the current study, 26.23% (19.85% underground workers and 6.38% surface workers) of workers had a habit of smoking, 68.08% (56.73% underground workers and 11.35% of surface workers) had a habit of regular consumption of alcohol and 6.37% (4.25% underground workers and 2.12% surface workers) of workers had an habit of intake of smokeless tobacco which are the major risk factors causing chronic diseases. Percentage of smokers and alcohol consumption is more than national average which is 10.7% and 30% respectively which may be due to social and cultural differences probably rather than occupation alone.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological distress levels arising from poor social networks have been noted to contribute to raised levels of mental stress and mental health issues in miners (Considine et al 2017). Chronic stress is a factor in a number of diseases, including anxiety, depression, sleep loss, all leading to poor memory and decision making; it impairs the immune system, increasing susceptibility to infections; it increases blood pressure, heart rate, cholesterol and triglycerides, contributing to heart disease, atherosclerosis, stroke, obesity and diabetes mellitus.…”
Section: Human and Socialmentioning
confidence: 99%